Low-cost and portable UV holographic microscope for high-contrast protein crystal imaging - Mustafa Ugur Daloglu; Aniruddha Ray; Michael J. Collazo; Calvin Brown; Derek Tseng; Blanca Chocarro-Ruiz; Laura M. Lechuga; Duilio Cascio; Aydogan Ozcan (APL Photonics, 2019)
Imaging protein crystals and distinguishing them from salt crystals is an important task for protein crystallographers. The conventional tool used for this purpose is a dual-mode microscope composed of bright-field and ultraviolet (UV) induced fluorescence modes. The distinction between a protein and a salt crystal is made based upon the fluorescence response to the UV excitation, where most protein crystals absorb the UV excitation and emit fluorescence, unlike salt crystals. These dual-mode optical microscopes are sensitive; however, they are relatively bulky and expensive as they require UV-grade optics. As an alternative, here we demonstrate that on-chip UV holographic imaging offers a low-cost, portable, and robust technique to image and distinguish protein crystals from salt crystals, without the need for any expensive and bulky optical components. Only composed of a UV light-emitting-diode at 280 nm and a consumer-grade complementary metal–oxide–semiconductor image sensor de-capped and interfaced to a Raspberry Pi single-board computer, the necessary information from the crystal samples (placed very close to the sensor active area) is captured in the form of in-line holograms and extracted through digital back-propagation. In these holographic amplitude reconstructions, protein crystals appear significantly darker compared to the background due to the strong UV absorption, unlike salt crystals which do not show any contrast, enabling us to clearly distinguish between them. We believe that the on-chip UV holographic microscope could serve as a low-cost, sensitive, and robust alternative to conventional lens-based UV-microscopes used in protein crystallography.